Peripancreatic Tuberculosis Lymphadenopathy: The Role of Endoscopic Ultrasound for Diagnosis - Hasan Maulahela; Achmad Fauzi (Interna Publishing, 2022)
Pancreatic and peripancreatic tuberculosis is a rare abdominal tuberculosis. Diagnosis for pancreatic tuberculosis can be challenging. Conventional imaging tools may show mass or malignancy in the pancreas. Endoscopic ultrasound (EUS) is an excellent tools for evaluating pancreas and peri pancreas region. It also allows us to obtain tissue sample for cytology and histopathology. Here we present a case of peripancreatic tuberculosis lymphadenopathy that mimic pancreatic mass. His symptoms were also nonspecific (weight loss, epigastric pain, and irregular fever). From EUS evaluation we found that there was no mass but multiple lymphadenopathy around the pancreas and then performed FNA. The result of the cytology was granuloma inflammation and caseous necrosis which is compatible with tuberculosis infection. From this case illustration we conclude that EUS is an important diagnostic tool for pancreatic lesion to avoid unnecessary surgery.